Safety Evaluation of a New Traditional Chinese Medical Formula, Ciji-Hua'ai-Baosheng II Formula, in Adult Rodent Models. (14th January 2019) - Fu, Biqian; Zhai, Xiangyang; Xi, Shengyan; Yue, Lifeng; Wang, Yanan; Qiu, Yingkun; Gong, Yuewen; Xu, Yangxinzi; Qian, Linchao; Huang, Jingru; Lu, Dawei; Huang, Shuqiong; et al.
Abstract : Background . Ciji-Hua'ai-Baosheng II Formula (CHB-II-F) is a new traditional Chinese medical formula that has been shown to reduce toxicity and side effects of chemotherapy and increase the probability of cancer patient survival. Whether CHB-II-F is safe as an adjunctive therapy for cancer patients receiving chemotherapy has yet to be determined. Purpose . To evaluate the acute and subchronic toxic effects of CHB-II-F in rodent models. Methods . In acute toxicity test, 24 Kunming mice were divided into 2 groups: untreated control and CHB-II-F 1.05 g/mL (31.44 g/kg) treated group. Treatment was administered to the treated group 3 times a day for 14 days. The overall health, adverse reactions, and mortality rate were documented. In subchronic toxicity test, 96 Sprague-Dawley rats were divided into 4 groups: untreated control, high dose CHB-II-F (H) (26.20 g/kg), medium dose CHB-II-F (M) (13. 10 g/kg), and low dose CHB-II-F (L) (6.55 g/kg) [equal to 24.375 g (dried medicinal herb)/kg] treated groups. Treated groups were given the treatments once a day for 4 weeks. The overall health and mortality rate were recorded every day. Body weight and food consumption were measured once a week. Hematologic and biochemical parameters, organ weights, and histopathologic markers were analyzed after 4 weeks. An additional 2 weeks were given as the treatment recovery period before end-point euthanization, and biochemical analyses were performed. Results . The maximum tolerated dose (MTD) of CHB-II-F on mice was found to be 94.31 g/kg [equal to 351 g (dried medicinal herb)/kg], which is 108 times the human adult dose. In the acute toxicity test, administration of CHB-II-F 31.44 g/kg showed no adverse effect and did not cause mortality. In the subchronic toxicity test, after 4 weeks of treatment, compared to the controls, total cholesterol (TCHO) level, cardiac and splenic indexes, body weights of female rats, and mean corpuscular hemoglobin concentration (MCHC) in the CHB-II-F (H) group were significantly increased; triglyceride (TG) in the CHB-II-F (M) group and liver and splenic indexes in the CHB-II-F (L) group were increased. After the two-week recovery period, biofluid analyses, food consumption, and histopathologic examinations showed no abnormalities. Conclusion . Administration of CHB-II-F had no obvious adverse effect on the overall health of rodent models. A daily maximum dose of less than 94.31 g/kg or 6.55 g/kg CHB-II-F for 4 continuous weeks was considered safe.